Effects of a deep-water running program on muscle function and functionality in elderly women community dwelling - Daisy Alberti; Leilane Lazarotto; Paulo Cesar Barauce Bento (Universidade Estadual Paulista (UNESP), 2017)
Abstract AIMS The aim of the study was to determine the effects of deep-water running on muscle function and functionality in community dwelling old women. METHODS Older women (n=19) were randomly assigned to one of the two groups: deep-water running (DWR: n=09, 64.33±4.24 years, 75.15±12.53 kg, 160.45±7.52 cm; or control group CG: n=10, 64.40±4.22 years, 74.46±12.39 kg, 158.88±5.48 cm). The DWR group carried out 18 weeks of deep-water running, twice/week 50 min sessions. Dynamic isokinetic strength for the lower limb and functionality was assessed before and after intervention. RESULTS DWR group increased peak torque, total work and average power of the knee and hip flexors and extensors. Additionally showed better performance on gait speed, timed up and go test, five-times-sit-to-stand-test repetitions from a chair as well as the six-minute walk test. CONCLUSION The deep-water running program was effective to improve muscle function and functionality.